2021
DOI: 10.3390/diagnostics12010050
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Model for Insomnia Disorder and the Respiratory Arousal Threshold Phenotype in Obstructive Sleep Apnea in the Taiwanese Population Based on Oximetry and Anthropometric Features

Abstract: Insomnia disorder (ID) and obstructive sleep apnea (OSA) with respiratory arousal threshold (ArTH) phenotypes often coexist in patients, presenting similar symptoms. However, the typical diagnosis examinations (in-laboratory polysomnography (lab-PSG) and other alternatives methods may therefore have limited differentiation capacities. Hence, this study established novel models to assist in the classification of ID and low- and high-ArTH OSA. Participants reporting insomnia as their chief complaint were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
(81 reference statements)
0
6
0
Order By: Relevance
“… 34 These ensemble learning approaches, thus, have been widely utilized to assist diagnosis and decision-making in different medical fields. 30 , 35 …”
Section: Discussionmentioning
confidence: 99%
“… 34 These ensemble learning approaches, thus, have been widely utilized to assist diagnosis and decision-making in different medical fields. 30 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the bootstrapping procedure and the number of decision trees in RF can be easily fine-tuned to avoid overfitting and maintain model stability [23]. Hence, the RF approach has been broadly employed for aiding medical diagnosis [24,25]. Compared with current machine learning approaches for screening OSA risk, the current models have some advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Another study used oximetry parameters during sleep and body profiles to differentiate between high- or low-ArTH OSA and insomnia. That study observed that patients with both high- and low-ArTH OSA had higher BMI and wider neck circumference and waist circumference compared with patients with insomnia [ 11 ].…”
Section: Introductionmentioning
confidence: 99%